Lenalidomide-Associated Secondary B-Lymphoblastic Leukemia/Lymphoma—A Unique Entity: A Report of Two Cases With Low-Level Bone Marrow Involvement and Review of the Literature. Issue 6 (3rd September 2020) - Germans, Sharon Koorse; Kulak, Ozlem; Koduru, Prasad; Oliver, Dwight; Gagan, Jeffery; Patel, Prapti; Anderson, Larry D; Fuda, Franklin S; Chen, Weina; Jaso, Jesse Manuel
Abstract: Objectives: Autologous stem cell transplant with lenalidomide maintenance therapy has greatly improved the relapse-free and overall survival rates of patients with multiple myeloma but also has been associated with an increased risk of secondary B-lymphoblastic leukemia/lymphoma (B-ALL). Methods: We report a comprehensive review of the clinicopathologic features of 2 patients with multiple myeloma who developed secondary B-ALL during lenalidomide maintenance. Results: Our observations showed that the disease may initially present with subtle clinical, morphologic, and flow-cytometric findings. The flow cytometry findings in such cases may initially mimic an expansion of hematogones with minimal immunophenotypic variation. Both patients achieved complete remission of secondary B-ALL after standard chemotherapy; however, one patient continues to have minimal residual disease, and the other experienced relapse. Next-generation sequencing of the relapse specimen showed numerous, complex abnormalities, suggesting clonal evolution. Conclusions: Our findings suggest the need for increased awareness and further study of this unique form of secondary B-ALL.